2019
DOI: 10.1177/1086296x19833292
|View full text |Cite
|
Sign up to set email alerts
|

A Research Review of Literacy Tutoring and Mentoring in Initial Teacher Preparation: Toward Practices That Can Transform Teaching

Abstract: Our goal through this literature review is to report and synthesize the findings from research into literacy tutoring and literacy mentoring in initial teacher preparation. We identified a total of 62 published articles that met our selection criteria. We identified four conceptual areas of focus to organize and represent our findings: (a) the structural and design features of the one-to-one or small-group experiences, (b) preservice teacher learning and growth within the tutorial/mentoring experience, (c) pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 46 publications
(134 reference statements)
0
31
0
Order By: Relevance
“…In light of the JAAL readership, we note that Hoffman et al. 's (2019) literature review on mentoring in teacher preparation found that only a few of the 60 studies focused on teacher preparation to work with youths in middle school and high school settings. We hope this commentary encourages readers of JAAL to consider transformative hybrid spaces as options for their work.…”
Section: The Context Of Moçambiquementioning
confidence: 97%
See 2 more Smart Citations
“…In light of the JAAL readership, we note that Hoffman et al. 's (2019) literature review on mentoring in teacher preparation found that only a few of the 60 studies focused on teacher preparation to work with youths in middle school and high school settings. We hope this commentary encourages readers of JAAL to consider transformative hybrid spaces as options for their work.…”
Section: The Context Of Moçambiquementioning
confidence: 97%
“…According to a review of research into the uses of hybrid spaces (Hoffman et al., 2019), hybrid spaces (often called tutoring in the literature) provide beginning teachers opportunities to grow in their knowledge of literacy, language, and word structure and in the use of particular pedagogical and instructional strategies. Hoffman et al.…”
Section: From Practicum Experiences To Practice‐based Experiences: Thmentioning
confidence: 99%
See 1 more Smart Citation
“…We also draw on literature that focuses on how it is that PTs learn through experiences, situated in practice (Grossman, 2011). Programs that accomplish these goals often include guided practicum, in which course instructors in clinical settings guide PTs in teaching and reflection (Hoffman et al, 2019). Although we know quite a bit about how teachers learn in clinical experiences within courses, less attention in the field of literacy has been paid to CTs’ guidance of practice in the classroom practicum setting.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sato, E., & Chen, J. C. (2019). Rise to the occasion: The trajectory of a novice Japanese teacher's first online teaching through action research.…”
mentioning
confidence: 99%